STRATEGI PEMASARAN PT. ASURANSI ALLIANZ LIFE SYARIAH KPM PAGARALAM - Nur Hamidah; Muhammad Saleh (STKIP Persada Khatulistiwa Sintang, 2023)
Increasingly more people are becoming aware of the value of having insurance protection, and the government is supporting the expansion of the life insurance sector. Due to the introduction of new companies, the competition in the sharia life insurance market is becoming more intense, necessitating the use of an effective and efficient marketing strategy by PT. Asuransi Allianz Life Syariah in order to remain competitive and hold onto its market share. The goal of this study was to ascertain the Allianz Life Syariah Insurance's Pagaralam City marketing strategy from a sharia perspective. This study falls under the category of qualitative research. Documentation, observation, and in-person interviews with managers, sales representatives, marketers, and employees are the approaches utilized to gather research data. This study uses an inductive, continuous analytical method with the intention of producing concepts. According to the data analysis, Allianz Life Syariah, Pagaralam City, has adopted the following marketing tactics: market segmentation, selling, service, and development. From a sharia perspective, Asuransi Allianz Life Syariah Kota Pagaralam's marketing approach is entirely compliant with syariah because its marketers constantly follow Islamic marketing principles